A new species of Psammobates (Reptilia: Testudinidae) from the early Pleistocene of South Africa. - Broadley, Donald G. (Bernard Price Institute for Palaeontological Research, 1997)
A new species of Psammobates Fitzinger is described from early Pleistocene cave deposits at Sterkfontein in the Gauteng Province of South Africa. It seems to be most closely related to P. oculiferus (Kuhl), which today occurs to the west and north of the type locality, but the proportions of its depressed carapace come closest to Homopusfemoralis Boulenger.
Main article
Keywords: Psammobates, Pleistocene, South Africa, Drimolen.